Relationship between unemployment and selected macroeconomic variables in Malaysia / Nurul Izzah Mohd Amin - Mohd Amin, Nurul Izzah (2022)
Economic growth plays an important role in affecting employment in Malaysia whether it is positive or negative way. From the statistics, employment in Malaysia can be measured by looking at the annual unemployment rate where it is relatively higher in the 1980s, reaching its peak in 1986 at 7.4% and during 2020 is the recorded the second higher rate with 4.5. this is because there are major events happened that led the macroeconomics factors fluctuated. Since the unemployment is related and influenced by the economic growths, thus changes in macroeconomics factors will also change the unemployment rate. Macroeconomic factors such as gross domestic product (GDP), foreign direct investment (FDI) and exchange rate (ER) as the independent variables and are used to perform this research. unemployment rate as dependent variables w. This study examined data analysis considerations, such as descriptive analysis, which aided in data distribution and the detection of errors and typos. Furthermore, regression analysis and diagnostic test are utilised to quantify data into a single equation to explain how changes in the independent variable affect the dependent variables.